Intracerebral haemorrhage, anticoagulation and mechanical heart valves: what should I do next? - Shah, R (BMJ Publishing Group, 2013)
Life-long oral anticoagulant therapy is recommended to all patients with mechanical heart valves to reduce the incidence of thromboembolic events. However, intracerebral haemorrhage is the fatal complication associated with anticoagulation, with an estimated 6-month mortality of 67%. (1) The incidence of cerebral bleeding while on anticoagulation is 0.3–0.7%/year, with as many as 85% of survivors left with permanent neurological deficits. (2) Difficulties in management arise when anticoagulation is temporarily discontinued as mechanical valves, particularly mitral, are exposed to significant thromboembolic and valve dysfunction risk. The decision on when to appropriately restart anticoagulation needs to be balanced with the risk of precipitating further cerebral haemorrhage. There are currently no guidelines on the optimal time to start anticoagulation. We describe a case of the management approach implemented in a patient with a mechanical valve presenting to the emergency department with an acute intracerebral haemorrhage.